Current status and future trends of precision agricultural aviation technologies - Lan, Yubin; Shengde, Chen; Fritz, Bradley K (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Modern technologies and information tools can be used to maximize agricultural aviation productivity allowing for precision application of agrochemical products. This paper reviews and summarizes the state-of-the-art in precision agricultural aviation technology highlighting remote sensing, aerial spraying and ground verification technologies. Further, the authors forecast the future of precision agricultural aviation technology with key development directions in precision agricultural aviation technologies, such as real-time image processing, variable-rate spraying, multi-sensor data fusion and RTK differential positioning, and other supporting technologies for UAV-based aerial spraying. This review is expected to provide references for peers by summarizing the history and achievements, and encourage further development of precision agricultural aviation technologies.Keywords: precision agricultural aviation technology, remote sensing, aerial spraying, ground verificationDOI: 10.3965/j.ijabe.20171003.3088Citation: Lan Y B, Chen S D, Fritz B K. Current status and future trends of precision agricultural aviation technologies. Int J Agric & Biol Eng, 2017; 10(3): 1–17.